Correlation among experience of person-centered maternity care, provision of care and women’s satisfaction: Cross sectional study in Colombo, Sri Lanka - Rishard, M.; Fahmy, F.F.; Senanayake, H.; Ranaweera, A.K.P.; Armocida, B.; Mariani, I.; Lazzerini, M. (PLOS One, 2021)
Abstract Person-centered maternity care (PCMC) is defined as care which is respectful of and responsive to women's and families' preferences, needs, and values. In this cross-sectional study we aimed to evaluate the correlations among the degree of PCMC implementation, key indicators of provision of care, and women's satisfaction with maternity care in Sri Lanka. Degree of PCMC implementation was assessed using a validated questionnaire. Provision of good key practices was measured with the World Health Organization (WHO) Bologna Score, whose items include: 1) companionship in childbirth; 2) use of partogram; 3) absence of labor stimulation; 4) childbirth in non-supine position; 5) skin-to-skin contact. Women's overall satisfaction was assessed on a 1-10 Likert scale. Among 400 women giving birth vaginally, 207 (51.8%) had at least one clinical risk factor and 52 (13.0%) at least one complication. The PCMC implementation mean score was 42.3 (95%CI 41.3-43.4), out of a maximum score of 90. Overall, while 367 (91.8%) women were monitored with a partogram, and 293 (73.3%) delivered non-supine, only 19 (4.8%) did not receive labour stimulation, only 38 (9.5%) had a companion at childbirth, and 165 (41.3%) had skin-to-skin contact immediately after birth. The median total satisfaction score was 7 (IQR 5-9). PCMC implementation had a moderate correlation with women's satisfaction (r = 0.58), while Bologna score had a very low correlation both with satisfaction (r = 0.12), and PCMC (r = 0.20). Factors significantly associated with higher PCMC score were number of pregnancies (p = 0.015), ethnicity (p<0.001), presence of a companion at childbirth (p = 0.037); absence of labor stimulation (p = 0.019); delivery in non-supine position (p = 0.016); and skin-to-skin contact (p = 0.005). Study findings indicate evidence of poor-quality care across several domains of mistreatment in childbirth in Sri Lanka. In addition, patient satisfaction as an indicator of quality care is inadequate to inform health systems reform.
Keywords: Person-centered maternity care; Health facility; childbirth